Impact of Online Education on Nurses' Delivery of Smoking Cessation Interventions With Implications for Evidence-Based Practice - Bialous, Stella A; Sarna, Linda; Wells, Marjorie J; Brook, Jenny K; Kralikova, Eva; Pankova, Alexandra; Zatoński, Witold; Przewozniak, Krzysztof (Worldviews on evidence-based nursing, 2017)
BACKGROUND: Tobacco use is the leading cause of preventable disease and death in Europe and worldwide. Nurses, if properly educated, can contribute to decreasing the burden of tobacco use in the region by helping smokers quit smoking. AIMS: To assess: (a) the feasibility of an online program to educate nurses in Czech Republic and Poland on evidence-based smoking cessation interventions for patients and (b) self-reported changes in practices related to consistently (usually or always) providing smoking cessation interventions to smokers, before and 3 months after participation in the program. METHODS: A prospective single-group pre-post design. RESULTS: A total of 280 nurses from Czech Republic and 156 from Poland completed baseline and follow-up surveys. At 3 months, nurses were significantly more likely to provide smoking cessation interventions to patients who smoke and refer patients for cessation services (p < .01). Nurses significantly improved their views about the importance of nursing involvement in tobacco control. IMPLICATIONS FOR PRACTICE: Education about tobacco control can make a difference in clinical practice, but ongoing support is needed to maintain these changes. Health system changes can also facilitate the expectation that delivering evidence-based smoking cessation interventions should be routine nursing care. LINKING EVIDENCE TO ACTION: Educating nurses on cessation interventions and tobacco control is pivotal to decrease tobacco-related disparities, disease, and death. Online methods provide an accessible way to reach a large number of nurses.
Keywords: lékařská praxe založená na důkazech; dospělí; attitudes about smoking cessation; podpora zdraví; průzkumy a dotazníky; Female; Nurses; Tobacco Use Disorder; Health Promotion; Workforce; postoj zdravotnického personálu; Adult; ženské pohlaví; Surveys and Questionnaires; lidé; Evidence-Based Practice; nursing; odvykání kouření; Education; smoking cessation; kontinuální vzdělávání zdravotních sester; Attitude of Health Personnel; online education; tobacco use; prospektivní studie; Male; Prospective Studies; Czech Republic; výchova a vzdělávání; Internet; zdravotní sestry; poruchy vyvolané užíváním tabáku; Česká republika; pracovní síly; lidé středního věku; Education, Nursing, Continuing; nurses; mužské pohlaví; Poland; internet; Middle Aged; Smoking Cessation; Humans